Mechanistic Insights into the Photoisomerization of N, N′‐Disubstituted Indigos. Issue 26 (29th March 2022) - Budzák, Šimon; Jovaišaitė, Justina; Huang, Chung‐Yang; Baronas, Paulius; Tulaitė, Kamilė; Juršėnas, Saulius; Jacquemin, Denis; Hecht, Stefan
Abstract: N, N′ ‐disubstituted indigos are photoswitchable molecules that have recently caught the attention due to their addressability by red‐light. When alkyl and aryl groups are utilized as the N ‐substituents, the thermal half‐lives of Z isomers can be tuned independently while maintaining the advantageous red‐shifted absorption spectra. To utilize these molecules in real‐world applications, it is of immense importance to understand how their molecular structures as well as the environment influence their switching properties. To this end, we probed their photoisomerization mechanism by carrying out photophysical and computational studies in solvents of different polarities. The fluorescence and transient absorption experiments suggest for more polar excited and transition states, which explains the bathochromic shifts of absorption spectra and shorter thermal half‐lives. On the other hand, the quantum chemical calculations reveal that in contrast to N ‐carbonyl groups, N ‐alkyl and N ‐aryl substituents are not strongly conjugated with the indigo chromophore and can thus serve as a tool for tuning the thermal stability of Z isomers. Both approaches are combined to provide in‐depth understandings of how indigos undergo photoswitching as well as how they are influenced by N ‐substituent and the chemical surroundings. These mechanistic insights will serve as guiding principles for designing molecules eyeing broader applications. Abstract : Indigo photoswitches can undergo photoisomerization triggered by red‐light, which is of immense potential in applications such as biomedical research and material science. In this mechanistic investigation, the influence of chemical environment and N ‐substituents is elucidated through photophysical and computational approaches. This study further provides insights into the course of photoisomerization.